Delegated Monitors, Large and Small: Germany's Banking System, 1800-1914. - Guinnane, Timothy W. (Journal of Economic Literature, 2002)
Germany's financial system differs in many respects from those of the United States or Britain. One key difference is the banking system, which plays a relatively greater role in Germany. Germany has long had universal banks, institutions that provide a full range of financial services. Some economic historians attribute Germany's economic success, in part, to these institutions. In the United States arguments for the deregulation of banking often stress the supposed advantages of German-style universal banks. A long tradition in economic history focuses on close connections between large banks and industrial firms that allegedly allowed the banks to play an unusual role in industrial finance. This view of the German banking system misses some important parts of the story, including the relatively late development of the current institutions and the important role of other banking institutions such as savings banks and credit cooperatives. This paper traces the development of the German banking system in the century prior to World War I, stressing those aspects of the history that inform both discussions in the economics of information and banking, and debates about the deregulation of banking today.